Can the increase in atmospheric temperature enhance the toxicity and risk of fipronil for collembolans in tropical soils? - Hennig T.B.* (2022)
© 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.We evaluated the toxicity and risk (via toxicity exposure ratio approach — TER) of the insecticide fipronil to collembolan’s growth and reproduction in three tropical soils, under increasing atmospheric temperatures. Chronic toxicity tests were performed with Folsomia candida in tropical artificial soil (TAS), oxisol, and entisol spiked with increasing concentrations of fipronil, at three room temperature scenarios: a standard (20 ± 2 °C), a tropical condition (25 ± 2 °C) and a global warming simulation (27 ± 2 °C). Temperatures influenced the fipronil effects on the species reproduction differently between soil types. In TAS and oxisol the highest toxicities (EC50-based) were found at 27 °C (EC50 TAS = 0.81, 0.70, 0.31 mg kg−1; EC50 OXISOL = 0.52, 0.54, 0.40 mg kg−1; at 20, 25, and 27 °C, respectively). In entisol, the toxicity at 27 °C was lower compared to 25 and 20 °C (EC50 ENTISOL = 0.33, 0.24, 0.12 mg kg−1, respectively). Fipronil concentrations also increased the proportion of small juveniles (growth reduction) in all tested soils. However, this effect was greater (EC10-based) at higher temperatures (25 and/or 27 °C), regardless of the soil type. TER approach revealed a significant risk of fipronil in entisol, regardless of the tested temperature, while in other soils the risk was found significant only at the higher temperatures (25 and 27 °C for TAS, and 27 °C for oxisol). These results indicate that exposures to fipronil at high temperatures (e.g., those resulting from climate change) can threaten F. candida populations, depending on the soil type.